Fullerene–Ionic‐Liquid Conjugates: A New Class of Hybrid Materials with Unprecedented Properties. Issue 8 (14th January 2015) - Campisciano, Vincenzo; La Parola, Valeria; Liotta, Leonarda F.; Giacalone, Francesco; Gruttadauria, Michelangelo
Abstract A modular approach has been followed for the synthesis of a series of fullerene–ionic‐liquid (IL) hybrids in which the number of IL moieties (two or twelve), anion, and cation have been varied. The combination of C60 and IL give rise to new unique properties in the conjugates such as solubility in water, which was higher than 800 mg mL−1 in several cases. In addition, one of the C60–IL hybrids has been employed for the immobilization of palladium nanoparticles through ion exchange followed by reduction with sodium borohydride. Surprisingly, during the reduction several carbon nanostructures were formed that comprised nano‐onions and nanocages with few‐layer graphene sidewalls, which have been characterized by means of thermogravimetric analysis (TGA), X‐ray photoelectron spectroscopy (XPS), X‐ray diffraction (XRD), scanning electron microscopy/energy‐dispersive X‐ray analysis (SEM‐EDAX), and high‐resolution transmission electron microscopy (HRTEM). Finally, the material thus obtained was successfully applied as catalyst in Suzuki and Mizoroki–Heck reactions in a concentration of just 0.2 mol %. In the former process it was recyclable for five runs with no loss in activity.